Day 4 Wed, October 16, 2019 2019
DOI: 10.2118/198000-ms
|View full text |Cite
|
Sign up to set email alerts
|

Low-Salinity Polymer Flooding in a High-Temperature Low-Permeability Carbonate Reservoir in West Kuwait

Abstract: While polymer flooding has widely been used as a successful technology to improve mobility control and sweep efficiency in many oil reservoirs, its applicability under harsh temperature/salinity conditions and in low-permeability reservoirs has prohibitively remained a challenge. This study was aimed at investigating the feasibility of low-salinity polymer flooding in a very challenging reservoir located in Kuwait with low permeability (< 10 mD), high temperature (113°C), high salinity (~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The limitations of standalone PF can be overcome by combining it with EW or LSW, and this has been given the term 'hybrid engineered water polymer flooding' (EWPF). The effectiveness of EWPF in carbonates has been proven by various experimental [61][62][63][64][65] and numerical modeling [66][67][68][69] studies. EWPF provided incremental recovery of 10% OOIP from carbonate cores in experiments by Al Sofi et al [70].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The limitations of standalone PF can be overcome by combining it with EW or LSW, and this has been given the term 'hybrid engineered water polymer flooding' (EWPF). The effectiveness of EWPF in carbonates has been proven by various experimental [61][62][63][64][65] and numerical modeling [66][67][68][69] studies. EWPF provided incremental recovery of 10% OOIP from carbonate cores in experiments by Al Sofi et al [70].…”
Section: Introductionmentioning
confidence: 99%
“…EW aids in altering the carbonate rock wettability by desorption of acidic crude oil components [71,72], and PF helps in providing stable oil bank displacement by creating a favorable mobility ratio [73]. The adsorption and chemical degradation of HPAM polymer is also reduced in the presence of EW, and therefore, less polymer is required to achieve a desired viscosity [62]. A 30-50% reduction in polymer concentration can be achieved by combining EWF and PF, due to a higher solution viscosity and lower polymer adsorption under low-salinity settings [62,65,74].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Al Murayri et al [ 184 ] indicated that the most common deterrents under the HTHS conditions are low-permeability carbonates, which may be addressed by carefully selecting the polymer/ solvent/ co-solvent, pre-shearing, and suitable design of low salinity polymer-based cEOR [ 184 ]. They demonstrated that injecting polymer at 113 C in a reservoir with less than 10 mD permeability was possible in their investigation, which was a long-term stability test [ 184 ]. Based on the composition of the injected brine, rheological tests revealed that when the polymer solution had a viscosity of 2–3 cP, a stable flood could be achieved with 2500–4000 ppm polymer.…”
Section: Experimental Laboratory Studiesmentioning
confidence: 99%
“…Based on the composition of the injected brine, rheological tests revealed that when the polymer solution had a viscosity of 2–3 cP, a stable flood could be achieved with 2500–4000 ppm polymer. As a result, combining thorough laboratory tests and design with low-salinity water floods proved to be extremely beneficial [ 184 ].…”
Section: Experimental Laboratory Studiesmentioning
confidence: 99%